PENENTUAN KADAR FENOL TOTAL DAN UJI AKTIVITAS ANTIOKSIDAN KOMBINASI EKSTRAK ETANOL DAUN MINT (MENTHA PIPERITA L.) DAN DAUN KEMANGI (OCIMI BASILICI F. CITRATI FOLIUM) DENGAN METODE DPPH - Olidermawanto Telaumbanua; Nerly Juli Pranita Simanjuntak; Erida Novriani (Journal of Innovative and Creativity, 2026)
Amid the rising incidence of degenerative diseases due to oxidative stress in Indonesia, natural antioxidants from mint leaves (Mentha piperita L.) and basil (Ocimum basilicum f. citrati) have potential as an alternative. This laboratory quantitative experimental study aimed to determine the total phenolic content and antioxidant activity of a 1:1 ethanol extract combination using the Folin-Ciocalteu and DPPH methods. The population was fresh leaves from Medan, with 1 kg of dried simplicia samples each selected purposively. Instruments used included a UV-Vis spectrophotometer (730 nm for phenolics, 517 nm for DPPH), linear regression analysis of the calibration curve (R²=0.965), and triplicate IC50 data. Results showed a total phenolic content of 19.16 ± 1.08 mg GAE/g and very strong antioxidant activity (IC50 9.891 µg/mL), exceeding the 50 µg/mL threshold though lower than vitamin C (4.852 µg/mL), confirming phenolic synergy. In conclusion, the combination has high potential as an anti-degenerative phytopharmaceutical.